AN ASSESSMENT OF ARCHITECTURE STUDENTS' PERCEPTION ON THE SOFT AND PRACTICAL SKILLS INTEGRATION INTO THE CURRICULUM STRUCTURE FOR SUSTAINABLE DEVELOPMENT IN NIGERIA - Raji, Abdulazeez Umar; Gafar, Mudashir (Journal of Technology Management and Business, 2018)
Graduates' unemployment is a critical issue in Nigeria. The government and Higher Learning Institutions (HLIs) emphasis on the soft and practical skills integration in the curriculum structure is to turn out graduates with balanced capacities, diversities and flexibilities to survive the competitive labour market. Even though, little empirical findings are available on the level of soft and practical skills integration in the Nigeria public universities, particularly architecture programmes, the construction industry is seen as a major contributor to national economic development. Contemporary skills requirement for the graduating architects' self-empowerment is still contentious in the academic circle. This paper aimed to propose Architects' Career Skills Development (ArCaSD) assessment model and ten hypotheses were postulated to test the model. It is premised that the architecture students' perception on the level of infusion and acquisition of the entire range of soft skills and practical workshop practice embedded in the architecture's curriculum structure for self-empowerment be evaluated. Quantitative research methodological approach and structural equation modelling were employed to analyse the data collected from 153 students. The finding showed that all the ten hypotheses were supported and positively significant. In addition, the perception of the students on the soft skills integration is substantially positive and above average. The findings further indicates that, despite the practical skills acquisition, there is need to focused more on the architectural design rather than combining it with practical training in entrepreneurship and pragmatic workshop practice. In conclusion, students' narrow-mindedness on the importance of entrepreneurship and practical skills development call for innovation in architecture's curriculum structure and pedagogical approach to facilitates capacity building for employment creation and national economic development in Nigeria.